Laser-induced voltage of shale due to photothermal effect. (3rd August 2021) - Peng, Xue; Miao, Xinyang; Liu, Xuecong; Lu, Wanting; Zhang, Shanzhe; Zhan, Honglei; Yue, Wenzheng; Zhao, Kun
Abstract: In this paper, the laser-induced voltage (LIV) of the shale has been investigated under the irradiation of a 532 nm laser. The LIV on the shale was temperature dependent. The thermal model based on the heat conduction equation provided an explanation for the LIVs and a double exponential model was used to describe the voltage rise process. With its advantage of rapidness, collimation, and no contact, the LIV technology may serve as a powerful tool to reveals information about optical and thermal properties of shale.